(untitled) (Journal of Indonesian Active in Sports, 2025)
This study investigated the effects of harlan cohen’s and two-pass reaction on the setting skills of volleyball players at GAPERTA VC, Medan. A pretest-posttest experimental design was used, involving 10 male players who were evenly divided into two groups based on pretest rankings. Group A practiced harlan cohen’s, focusing on agility and coordination, while Group B practiced the two-pass reaction, which emphasized quick decision-making and adaptability. The training program lasted six weeks, consisting of 18 sessions. Standardized assessments were conducted before and after the intervention, and the data were analyzed using paired and independent sample t-tests at a significance level of α = 0.05. The results showed that both drills significantly improved setting skills. Harlan cohen’s drill enhanced technical fundamentals, such as precision and control, whereas the two-pass reaction drill improved reaction time and situational awareness. Despite these distinct focuses, the independent sample t-test revealed no significant differences in the effectiveness of the two methods, suggesting their complementary potential. This study concludes that integrating these drills into training regimens can provide a comprehensive approach to developing both technical and tactical volleyball skills. The findings offer valuable insights for coaches seeking to optimize player performance through targeted training methods. Future research is encouraged to explore larger sample sizes and additional training variations to further validate and expand upon these results.